Lockende Berge - Maeder, Herbert 1930-2017 (Backbonebooks-Verlag, 2021)
For Stroma, Claudia de la Torre reproduced 1 to 1 the picture book "Lockende Berge" published in 1971 by Linda Verlag, and re-published it in an edition of 15 copies. The book is filled with stories and footnotes pointing to empty spaces framed by marks intended to show where the images should be glued on. A blurb text of the book can be read, framing the space of the window as parenthesis - Waiting for the public to fill in the blanks
Auflage 15 Ex., nummeriert
Keywords: Torre, Claudia de la -- 1986-; Künstlerbuch